Generation of High Expressing Chinese Hamster Ovary Cell Pools Using the Leap‐In Transposon System. Issue 10 (11th June 2018) - Balasubramanian, Sowmya; Peery, Robert B.; Minshull, Jeremy; Lee, Maggie; White, Regina; Kelly, Ronan M.; Barnard, Gavin C.
Abstract : Clonally derived cell lines (CDCL) from Chinese Hamster Ovary (CHO) host cell lines, remain the most popular method to manufacture therapeutic proteins. However, CHO cell pools are increasingly being used as an alternate method to produce therapeutic proteins for preclinical drug development in an effort to shorten the time required for new drug development. It is essential that these CHO pools exhibit the desired attributes of CHO CDCLs such as high protein titers and consistent product quality attributes (PQAs). In this study the authors evaluated the Leap‐In Transposase®, for the expression of four different proteins (three mAbs and one Bispecific mAb). The resultant pool titers ranges from 2.0 to 5.0 g L −1 for the four proteins compared to 1.5–3.3 g L −1 from the respective control pools (generated by random gene integration). The resultant cell pools are a homogeneously expressing cell population. The average gene copy numbers are similar or lower in the evaluation pools relative to the control pools. The higher titers in the evaluation pools are attributed to higher levels of both IgG‐LC and IgG–HC mRNA. In conclusion, the Leap‐In transposase generates high titer, homogeneous CHO pools in a short time‐period without introducing any undesired PQAs. Abstract : CHO pools that exhibit the desired attributes of CHO cell lines offer an attractive alternative to produce therapeutic proteins for preclinical drug development. In this study, the authors evaluate the novel Leap‐In transposon system and demonstrate that Leap‐In generates high titer cell pools with desirable PQAs. The high titers are attributed to higher levels of gene transcript and a homogeneously expressing cell population.